Worry about COVID-19 in relation to cognitive-affective smoking processes among daily adult combustible cigarette smokers. Issue 4 (4th July 2021) - Shepherd, Justin M.; Fogle, Brienna; Garey, Lorra; Viana, Andres G.; Zvolensky, Michael J.
ABSTRACT: Cigarette smoking is a known risk factor for severe disease and death from respiratory infection. Initial data suggest that smoking is a risk factor for COVID-19 symptom severity. Exposure to increased pandemic-related stress and subsequent worry about COVID-19 may amplify the desire to smoke to down-regulate distress. The present investigation sought to test this conceptual model by evaluating worry about COVID-19 in relation to COVID-19 coping motives for smoking, perceived barriers for smoking cessation, and smoking abstinence expectancies. Participants were 219 daily combustible cigarette smokers (55.70% female, Mage = 41.43 years, SD = 11.06). Six separate, two-step hierarchical linear regression models were conducted for each of the criterion variables. As expected, worry about COVID-19 was significantly and positively related to COVID-19 coping motives for smoking and perceived barriers for smoking cessation. Worry about COVID-19 also was a positively significant predictor of smoking abstinence expectancies of negative mood, somatic symptoms, and harmful consequences, but not positive consequences. The present study provides novel empirical evidence that worry about COVID-19 is related to key cognitive-affective smoking processes beyond the effects of age, sex, race, ethnicity, COVID-19 exposure, smoking rate, e-cigarette use status, and anxiety symptoms. These results highlight the potential utility in assessing level of worry about COVID-19, a transdiagnostic construct, among combustible cigarette smokers to better understand cognitive-affective factors that may maintain smoking behavior in the context of the COVID-19 pandemic.